Supermagnetic nano-bifunctional catalyst from rice husk: synthesis, characterization and application for conversion of used cooking oil to biodiesel - Hazmi, Balkis; Rashid, Umer; Yap, Taufiq Yun Hin; Ibrahim, Mohd Lokman; Nehdi, Imededdine Arbi (MDPI, 2020)
The present work investigated the biodiesel production from used cooking oil catalyzed by nano-bifunctional supermagnetic heterogeneous catalysts (RHC/K2O/Fe) derived from rice husk doped with K2O and Fe synthesized by the wet impregnation method. The synthesized catalysts (RHC/K2O/Fe) were characterized for crystallinity by X-ray diffraction spectroscopy (XRD), total acidity and basicity using CO2/NH3-TPD, textural properties through Brunauer-Emmett-Teller (BET), thermal stability via thermogravimetric analyzer (TGA), functional group determination by Fourier-transform infrared spectroscopy (FTIR), surface morphology through field emission scanning electron microscopy (FESEM), and magnetic properties by vibrating sample magnetometer (VSM). The VSM result demonstrated that the super-paramagnetic catalyst (RHC/K2O-20%/Fe-5%) could be simply separated and regained after the reaction using an external magnetic field. The operating conditions such as catalyst loading, methanol/oil molar ratio, temperature, and reaction duration were studied. The screened RHC/K2O-20%/Fe-5% catalyst was selected for further optimization and the optimum reaction parameters found were 4 wt % of catalyst, a molar ratio of methanol/oil of 12:1, 4 h reaction duration, and 75 °C reaction temperature with a maximal yield of 98.6%. The reusability study and reactivation results revealed that the nano-bifunctional magnetic catalyst (RHC/K2O-20%/Fe-5%) could be preserved by high catalytic activity even after being reused five times.